Combined Vojta and Bobath concepts therapy effect and physical exercises on foot balance and motor control in children with infantile cerebral palsy - Peter Bartik; Andreea Popescu; Camelia-Daniela Plăstoi; Bogdan Niculescu; Peter Šagát; Pablo Prieto González; Ibrahim AL Jasser; Dragoș Ioan Tohănean; Ioan Turcu; Eliška Kubíková (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Background: Ensuring independent locomotion is one of the primary goals of therapeutic intervention in children with infantile cerebral palsy (ICP). This study aimed to evaluate the foot and balance developmental changes in children with ICP after independent walking began utilizing Bobath, Vojta, and combined concepts for therapy.  Methodology: 12 children (5 girls, 7 boys) aged 2-5 years diagnosed with ICP were distributed into three groups. Group I – 4 subjects treated with Vojta therapy, Group II – 4 subjects treated with Bobath therapy, and Group III – 4 subjects treated with a combined therapy. The assessment of the subjects included the Berg scale, the Gross Motor Function Classification System (GMFCS), and a Stabilometry footboard PoData 2.00. Results: Group I reported an improvement in balance, and Group II reported an improvement in muscle tone. Group III reported a significant improvement in coordination and balance through rebalancing the plantar weight distribution on each leg.  Conclusions: This study highlights and recommends combining Bobath and Vojta's approaches for advanced impact on foot balance and motor control in children with infantile cerebral palsy.